Concurrent training in prepubescent children: the effects of 8 weeks of strength and aerobic training on explosive strength and VO2max - Alves, A. R.; Marta, C. C.; Neiva, H. P.; Izquierdo, M.; Marques, M. C. (The Journal of Strength and Conditioning Research, 2016)
The purpose of this study was to compare the effects of 8-week training periods of strength training alone (GS), combined strength and aerobic training in the same session (GCOM1), or in 2 different sessions (GCOM2) on explosive strength and maximal oxygen uptake (VO2max) in prepubescent children. Of note, 168 healthy children, aged 10-11 years (10.9 ± 0.5), were randomly selected and assigned to 3 training groups to train twice a week for 8 weeks: GS (n = 41), GCOM1 (n = 45), GCOM2 (n = 38) groups, and a control group (GC) (n = 44; no training program). The GC maintained the baseline level, and trained-induced differences were found in the experimental groups. Differences were observed in the 1 and 3-kg medicine ball throws (GS: +5.8 and +8.1%, respectively; GCOM1: +5.7 and +8.7%, respectively; GCOM2: +6.2 and +8%, respectively, p < 0.001) and in the countermovement jump height and in the standing long jump length (GS: +5.1 and +5.2%, respectively; GCOM1: +4.2 and +7%, respectively; GCOM2: +10.2 and +6.4%, respectively, p < 0.001). In addition, the training period induced gains in the 20-m time (GS: +2.1%; GCOM1: +2.1%; GCOM2: +2.3%, p < 0.001). It was shown that the experimental groups (GCOM1, GCOM2, and GS) increased VO2max, muscular strength, and explosive strength from pretraining to posttraining. The higher gains were observed for concurrent training when it was performed in different sessions. These results suggest that concurrent training in 2 different sessions seems to be an effective and useful method for training-induced explosive strength and VO2max in prepubescent children. This could be considered as an alternative way to optimize explosive strength training and cardiorespiratory fitness in school-based programs.